ESTIMATION OF CURRENT DYNAMICS AND FORECAST OF GLACIOLOGICAL CHARACTERISTICS OF THE MALYI AKTRU GLACIER (CENTRAL ALTAI) - V. V. Paromov; Yu. K. Narozhnyi; L. N. Shantykova (Лëд и снег, 2018)
In the context of global and regional climatic changes in the Altai mountain region, observations performed in 1949–2014 demonstrated evident rises of air temperatures, both annual and seasonal means. Relative to the climatic norm (1949–1985), mean annual temperature (averaged for the period 1986–2014) had risen by 0.8– 1.9 °С. The most significant warming took place in winter and spring. In winter, the positive difference with the mean value is approximately equal to 0.9–3.8 °C, while in spring 0.9 and 1.7 °C. Air temperatures in summer and autumn periods were rising as well. Changes in annual and seasonal precipitations were more variable. The autumn and winter periods are characterized by a decrease in precipitation. On average, it is respectively 17% and 6%. In the spring and summer seasons, the tendency is opposite since these periods are characterized by a weak increase in precipitation. On average for the whole territory, the increase in the mean climatic amount of seasonal precipitation was equal to 2% and 4% relative the climatic norm for 1966–1985, for spring and summer respectively. The amount of annual precipitation on theterritoryofGorny Altairemained unchanged. Under current climate conditions which are characterized by decreasing in winter precipitation, the air temperature rise during all seasons, and longer warm period the mass balance of the Malyi Aktru Glacier becomes drastically negative. Total accumulation decreases, the ablation increases, and as a result, the negative mass balance grows. Using the methods of exponential smoothing, given the type of the trend component in series of meteorological quantities, a forecast of a 10‑year mean air temperature and the amount of atmospheric precipitation was made for the period 2021–2030. Using the appropriate regression equations, this allowed calculating predictive mean values of accumulation, ablation, and mass balance of the Malyi Aktru Glacier for the third decade of the XXI century